Modifikasi Struktur Rangka Gedung Kuliah Fakultas Ekonomi Bisnis UPN “Veteran” Jawa Timur dengan Penambahan Tinggi Tingkat dan Balok Prategang - Rizka Abdillah Arisandi; Sumaidi Sumaidi; Cintantya Budi Casita (KERN, 2022)
Indonesia is a country that is frequently hit by earthquakes, so a method for planning and implementing earthquake-resistant development is needed. In this final project, modifications will be made to the building of the Faculty of Business Economics, UPN "Veteran" East Java, with a complete library on the 5th floor and increasing the level by 0.5 m and eliminating long-span columns. Buildings that have different levels of height with other levels can result in a soft story. Soft stories have an influence on the level of lateral stiffness that occurs on certain floors. Vertical irregularities result in differences in stiffness which have the potential for failure of the column which can cause the building to collapse. This design requires prestressed beams due to modifications to the 5th floor due to loss of columns in the span to support 21 m of free span. In its implementation, the prestressed beam method used is post-tension (post-tension). Performance Based Design (PBD) is an earthquake load design method for new buildings and for upgrading existing buildings. This study uses the Capacity Spectrum Method (CSM) to determine the performance of the structure by using pushover analysis. From the results of this study, the building ductility values ​​obtained were 4.53 for the X direction and 3.08 for the Y direction which were categorized as partial ductility. The resulting performance level is Damage Control (DC) for the X direction and the Immediate Occupancy (IO) performance level for the Y direction. These results describe the building structure in a stable and safe condition when receiving earthquake loads..